"Shop-lease Contract with Sar-qofli" in the Post-Iranian Revolution Era: Deletion of "Haqq-e kasb o pisheh o tejārat" from the Law of Lessor–Lessee Relationships. Issue 3 (May 2016) - Iwasaki, Yoko
Abstract : In contemporary Iran, many shops are under the "shop-lease contract with sar-qofli ." In this contract, sar-qoflisar-qofli, a strong usufructuary right supported by intangible assets such as the shop's reputation, is given to the tenant. The "shop-lease contract with sar-qofli " originated from a traditional merchants' custom in Iran's business quarters. After the 1979 Revolution, the Law of Lessor–Lessee Relationships, which provides a legal framework for the practice of "shop-lease contract with sar-qofli, " was completely revised, since Islamic jurists regarded haqq-e kasb o pisheh o tejārat as problematic. Haqq-e kasb o pisheh o tejārat, the legal designation of sar-qofli, was based on a heterogeneous value concept introduced into the Iranian legal system from abroad during World War II. As a result of this revision, another alternative for asset management was granted to shop owners. Nevertheless, "shop-lease contract with sar-qofli " remains the most widely employed form of lease in Iran's property lease market.